On bi-bases of ordered G-semigroups - Jantanan, Wichayaporn; Latthi, Monthean; Puifai, Jiriya (Naresuan University Journal: Science and Technology (NUJST), 2021)
In this paper, based on the results of ordered bi-ideals generated by a non-empty subset of an ordered G-semigroups ,  we introduce the concept of bi-base of M. Using the quasi-order on M defined by the principal ordered bi-ideals of M. we characterize when a non-empty subset of  M is a bi-base of M. The results obtained extending the results on G-semigroup. Keywords: ordered G-Semigroup, bi-G-ideal, bi-base, quasi-order